Spillover effects of blacklisting policy in the Brazilian Amazon - Andrade, Luiza Cardoso de (2016)
We analyse the effects of the Priority Municipalities List, that indicates the primary targets of environmental police monitoring, on deforestation of municipalities in the neighbourhood of the listed. We argue that being a neighbour to a priority municipality causes an exogenous variation in environmental authorities\' presence, and use a difference-in-differences estimator to determine the impact of such presence on deforestation. As an innovative feature, we introduce a spatial version of this estimator to correct spatial dependence. Our results show that the net effect of treatment is a decrease in deforestation of 19% to 23%. Estimates also indicate that effects get weaker the greater the distance to the priority municipality